Bisphenol A Release from Dental Composites and Resin-Modified Glass Ionomers under Two Polymerization Conditions - Tichy, Antonin; Simkova, Marketa; Vrbova, Radka; Roubickova, Adela; Duskova, Michaela; Bradna, Pavel (Polymers, 2021)
Bisphenol A (BPA)-based monomers are commonly contained in dental resin-based materials. As BPA is an endocrine disruptor, its long-term release from restorative composites and resin-modified glass ionomers (RM-GICs) under two polymerization conditions was measured in this study. Specimens of two conventional composites containing BPA-based monomers, two "BPA-free" composites, and two RM-GICs were polymerized from one side for 20 s at 1300 mW/cm2 or for 5 s at 3000 mW/cm2. The amounts of BPA released in artificial saliva and methanol after 1, 4, 9, 16, 35, 65, 130, and 260 days were measured using liquid chromatography-tandem mass spectrometry. The highest amounts of BPA were released from conventional composites, followed by RM-GICs, while the least was released from "BPA-free" composites. Amounts of released BPA were significantly higher in methanol and decreased gradually after the first day. Fast polymerization (5 s at 3000 mW/cm2) resulted in a significantly higher release of BPA after 1 day, but the effect of polymerization conditions was not significant overall. In conclusion, fast polymerization increased the initial release of BPA, but the released amounts were significantly lower than the current tolerable daily intake (4 μg/kg body weight/day) even in methanol, representing the worst-case scenario of BPA release.
Keywords: mass spectrometry; bisphenol A; light-curing; Bis-GMA; glass ionomer cements; resin composite; liquid chromatography